2018
DOI: 10.1002/jcp.26770
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin leads to cell death in endometriosis by regulation of endoplasmic reticulum stress and cytosolic calcium level

Abstract: Chrysin is a natural compound derived from honey, propolis, or passion flowers and has many functional roles, such as antiinflammatory and antiangiogenesis effects. Although endometriosis is a benign gynecological disease, there is a need to identify the pathology and develop a therapy for endometriosis. Elucidating the biological mechanism of chrysin on endometriosis will improve the understanding of endometriosis. In this study, we confirmed the apoptotic effects of chrysin in human endometriotic cells using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…A total of 286 studies were initially identified by the search criteria. After applying the selection criteria, a total of 60 trials were included in the systematic review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 286 studies were initially identified by the search criteria. After applying the selection criteria, a total of 60 trials were included in the systematic review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Ji and coworkers demonstrated that puerarin can partly suppress estrogen-stimulated proliferation by promoting the recruitment of corepressors to estrogen receptor, as well as limiting that of coactivators, in order to arrest ectopic stromal cells in the G1 phase [ 34 ]. Three studies out of 22 investigated the biological effect of chyrisin, a natural compound derived from honey, propolis, or passion flowers, on human endometrial cells [ 20 , 66 , 75 ]. Although shown to be potent inhibitor of aromatase activity in a free cell assay, chyrisin, daidzein or naringenin could not attenuate aromatase activity in endometrial stromal cells in women with and without endometriosis at any concentration tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts through the induction of apoptosis and inhibition of cancer cell migration [43,44]. Its antitumor properties were proven for various malignancies, including prostate cancer (DU 145, PC-3) [45], breast cancer [46], lung cancer (A549), liver cancer (HepG2), colon cancer (SW480) [47] and pancreatic cancer (SW1736, 8505C) [48], and also epidermoid carcinoma (A431) [49], glioblastoma (T98, U251, U87) [50] and human uveal melanoma (SP6.5, M17) [51]. According to the Salama and Allam study [52], chrysin and daidzein exerted anticancer activity against SW620 cells, which was associated with a decrease in the protein expression of p-ERK/ERK and p-AKT/AKT.…”
Section: Biological Activity 41 Anticancer Activity Of Chrysin and Its Derivativesmentioning
confidence: 99%
“…Chrysin may find an application in the treatment of gynecological diseases, such as endometriosis, which may lead to infertility. Research with the use of human endometriotic cells derived from the cervix (End1/E6E7) and vagina (VK2/E6E7) revealed that chrysin suppressed the proliferation and induced apoptosis of these cells by affecting the cell cycle, changing the cytosolic calcium level, affecting the generation of reactive oxygen species and by inactivating the PI3K signaling pathways [45].…”
Section: Other Biological Effects Of Chrysinmentioning
confidence: 99%